Facebook Groups as LMS: A Case Study - Meishar-Tal, Hagit; Kurtz, Gila; Pieterse, Efrat (International Review of Research in Open and Distributed Learning, 2012)
This paper describes a pilot study in using Facebook as an alternative to a learning management system (LMS). The paper reviews the current research on the use of Facebook in academia and analyzes the differences between a Facebook group and a regular LMS. The paper reports on a precedent–setting attempt to use a Facebook group as a course website, serving as a platform for delivering content and maintaining interactions among the students and between the students and the lecturer. The paper presents findings from the students’ self-assessments and reflections on their experience. The students expressed satisfaction with learning in Facebook and willingness to continue using these groups in future courses.